Effect of nanoparticles on the structure of thin films: atomistic simulation results - Grigoriev, F.V.; Sulimov, V.B.; Tikhonravov, A.V. (Numerical Methods and Programming (Vychislitel’nye Metody i Programmirovanie), 2018)
A model describing the effect of nanoparticles on the structure of thin films structure is proposed. The model is based on the previously developed molecular dynamics method of thin film deposition simulation and is applied to the study of silicon dioxide thin films. A nanoparticle is considered as a fixed object whose interaction with film atoms is described by a spherical symmetric potential. Radial distribution functions are used to study the film structure near the nanoparticle. It is shown that the behavior of these functions is essentially different near nanoparticles in the cases of high-energy and low-energy deposition processes.